Organic contaminants of emerging concern in the Awash River basin - Hailu, K; Birhanu, B; Kebede, S (University of Oxford, 2024)
Emerging Organic Contaminants (EOCs) affecting freshwater quality have become a rising concern due to adverse effects on human health and the environment. In this research, we characterized EOCs in the water supply sources (boreholes, surface water reservoirs, and river) and tap waters in upper Awash River sub-basin, Ethiopia. The Awash River basin is a rapidly growing and highly utilized and industrialized catchment in central Ethiopia where both surface and groundwater are used to supply major settlements and industries. The characterization of the EOCs was supplemented by hydro-chemical analysis (major anions, cations, heavy metals). Environmental isotopes (2H, 18O, and 222Rn) were used to further investigate the exchange of contaminants between surface and groundwater supply sources. More than 100 EOCs are identified in all water supply sources and tap water. The EOCs are linked to agricultural applications pesticides, herbicides, veterinary drugs, and plant growth regulators), urban (artificial sweeteners, pharmaceuticals, personal care products), and industries (surfactants, flame retardants, plasticizers, and volatile solvents). Based on the analysis of hydro-chemical and environmental tracers, the deep groundwater system has greater protection from contamination than the river and the shallow groundwater system. Due to connectivity with surface waters, the shallow aquifers are noticeably affected by urban, industrial, and agricultural pollutants. Attributed to the different contaminant sources, distinct variations in terms of compound types were observed at different locations. Upstream water supply sources are dominated by urban and industrial contaminants while compounds from agricultural applications dominate the downstream sites. Artificial infrastructures (i.e. Aba Samuel and Koka reservoirs) serve as attenuation points for urban and industrial sourced compounds. Characterization of EOCs showed new contaminant loads in the water supply sources in Ethiopia, which haven’t been tested before, with potential impact on human and wider environmental health, necessitating a revision of the customary water quality test and monitoring practices. Sampling took place between September 2019 and December 2022.